2012
DOI: 10.1177/0883073811435243
|View full text |Cite
|
Sign up to set email alerts
|

Combined ω3 and ω6 Supplementation in Children With Attention-Deficit Hyperactivity Disorder (ADHD) Refractory to Methylphenidate Treatment

Abstract: Children (6-12 years) with attention-deficit hyperactivity disorder (ADHD) being treated with methylphenidate and standard behavior therapy for more than 6 months, whose parents reported no improvement in behavior and academic learning, were randomly assigned to receive supplementation with a combined ω3 and ω6 preparation or a placebo. Outcome was measured at 3 and 6 months after treatment using a self-assessment checklist completed by the parents. Statistically significant improvement was found in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…showing some improvements (195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205) and others finding no effect (206)(207)(208)(209)(210)(211)(212)(213)(214) . These trials have been reviewed many times, with differing conclusions.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…showing some improvements (195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205) and others finding no effect (206)(207)(208)(209)(210)(211)(212)(213)(214) . These trials have been reviewed many times, with differing conclusions.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…We added 5 studies that none of the other meta-analyses used. Three of these are relatively new reports that met our criteria for inclusion (Milte et al, 2012; Perara, Jeewandara, Seneviratne, & Guruge, 2012; Richardson, Burton, Sewell, Spreckelsen, & Montgomery, 2012). As far as we can tell, should they have been published at the time, they would have met the inclusion criteria for one or more of the prior meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that an n-3 PUFA deficiency may lead to a variety of neuronal and psychological abnormalities, such as attention-deficit hyperactivity disorder, depression, schizophrenia, autism and anxiety [1,11,12,[15][16][17][18][19]. N-3 PUFA deficiency in rodents can result in hyperactivity, a feature underlying these neuropsychiatric disorders [14,20,21].…”
Section: Introductionmentioning
confidence: 99%